Psychometric properties of the A-D questionnaire (antisocial-delinquent behaviors) in high school students of educational institutions in the district of Comas, 2017 - Pérez Vásquez, Erik Roger (2017)
The purpose of this study is to know the psychometric properties of the AD (anti-social and criminal behavior) questionnaire (Nicolas Seisdedos ,1988). Data was collected from 200 students of high school in Comas (district of Lima) aged from 14 to 17. The results showed a validity on 37 items (V-Aiken>0,80), which were applied to the sample, and as a result, adequate reliability values were obtained (ritc>0,20) in the two scales (anti-social and criminal behavior). Moreover, the concurrent validity of the criteria was conducted by means of the correlation with a questionnaire adapted to the study population, obtaining acceptable values that confirmed the criteria validity. Finally, 33 items were obtained by the AD questionnaire and it was divided into two scales: anti-social behavior (19 items) and criminal behavior (14 items). In conclusion, the validated questionnaire offers psychometric properties that are adequate for the use of samples with similar characteristics. It is recommended to extend the study for the factorial, exploratory and confirmatory analysis of the instrument.